Gender Mainstreaming in Bureaucracy: A Bibliometric Analysis of the Past Two Decades - Wildan Maulana; Muh Azis Muslim (Green Publisher Indonesia, 2026)
Over the past two decades, gender mainstreaming in bureaucracy has received increasing attention in public policy and governance studies. This concept highlights the importance of inclusive policies in governance to create a fair and participatory space without gender discrimination. This study aims to understand the direction and development of research related to gender mainstreaming in bureaucracy through a bibliometric approach. An analysis was conducted of 35 scientific articles indexed in the Scopus database from 2004 to 2024. The data was then processed and visualized using the VOSviewer application to identify publication trends; research trends in global, regional, and local contexts; influential journals; authors and countries of major contributors; and potential future research themes. The results of this study revealed five main findings. First, there has been quite sharp fluctuation in this topic, but there are indications of a potential upward trend. Second, there is a tendency for differences in the implementation of gender mainstreaming in global, regional, and local contexts, emphasizing policy adaptation. Third, Comparative European Politics, Gender Work and Organization, and Canadian Public Administration are influential journals in terms of citations, publications, and influential articles. Fourth, the largest contributions came from academics in the UK and the United States. Fifth, several topics were found to be underexplored, such as